Square Slotted Patch Antenna for 2.45 GHz Far-field Wireless Power Transfer - Kulkarni, Shashank S.; Baghel, Amit Kumar; Nayak, Sisir Kumar (2019 IEEE International Conference on Microwaves, Antennas, Communications and Electronic Systems (COMCAS), 2019)
A square slotted patch antenna for far-field wireless power transfer applications is presented. The antenna has compact size equal to 0.416 × 0.236 × 0.013 λ which can be fit into most of the devices. It exhibits a total of 780 MHz of -10 dB impedance bandwidth in S-band with good directional characteristics. A maximum of 1.24 dB gain is observed with 1.025 dB at 2.45 GHz. A prototype of the antenna is fabricated and tested for S-band with good agreement between measured and simulated results. A computed study for far field WPT based on Friis transmission equation is presented for double ridged guide and parabolic profile horn as transmitting antennas.